Holland Family : Lay Down My Sword and Shield - Book 1 - Burke, James Lee 1936-; Patton, Will (New York , NY Simon & Schuster Audio, 2010)
Hack Holland, Texan and political candidate, becomes involved with civil rights which forces him to assess his priorities.
Unabridged.
Compact discs.
Read by Will Patton.
Keywords: Politicians -- Fiction -- Texas; Audiobooks; Texas -- Fiction -- Politics and government